Implementasi Manajemen Berbasis Sekolah Dalam Meningkatkan Kualitas Pembelajaran IPAS di SD Negeri 8 Timporongan - Citrayanti MK; Muh Yunus; Syarifuddin Syarifuddin (CV. Rayyan Dwi Bharata, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) in improving the quality of Natural and Social Sciences (IPAS) learning at SD Negeri 8 Timporongan, Pangkajene and Islands Regency. Specifically, this study seeks to describe the implementation of SBM in curriculum management and IPAS learning, teacher resource management, as well as the management of learning facilities and infrastructure. In addition, this study aims to identify the constraints faced by teachers and school management in implementing SBM and to examine the forms of parental participation in supporting SBM implementation in IPAS learning. This study employed a qualitative approach with a case study design. The research subjects included the principal, IPAS teachers, students, and parents of students at SD Negeri 8 Timporongan. Data were collected through in-depth interviews, classroom observations of IPAS learning, and documentation studies of relevant school documents. Data validity was ensured through source and method triangulation, member checking, and peer review. Data analysis was conducted using the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion drawing carried out interactively and continuously. The results of the study indicate that the implementation of School-Based Management at SD Negeri 8 Timporongan has been carried out fairly well in supporting the improvement of IPAS learning quality. The school provides flexibility for teachers to develop contextual IPAS learning based on the surrounding environment. The principal plays an active role as an instructional leader in encouraging the improvement of teacher competence; however, several constraints remain, including limited instructional time, high administrative workload for teachers, and limited learning facilities. Parental participation is manifested through regular communication, learning assistance at home, and involvement in school activities. Overall, the implementation of SBM has had a positive impact on the quality of IPAS learning, although continuous strengthening is still needed to optimize its implementation.